ANALISIS SISTEM ANTRIAN PADA STASIUN PENGISIAN BAHAN BAKAR (SPBU) KOPKAR NUSA TIGA JL. SUNGGAL MEDAN - Tinambunan, Anitha Paulina (UNIKA Santo Thomas, 2016)
This study aims to analyze the model of queues at filling stations Kopkar Nusa Three Jl. Sunggal Medan using phase.Teknik single multi-channel data collection is done through observation and documentation. The study population was the whole vehicle wheel 2 (two) in the queuing system on weekdays applicable on Nusa Tiga Kopkar gas station Jl. Sunggal Medan. Sampling is done by nonprobability sampling Convenience sampling using primary data obtained from observation. So the data is taken against vehicles entering into the queuing system is running. From the analysis of the queuing system Kopkar Nusa Three gas station Jl. Terrain Sunggal known Poisson distributed arrival frequency, level of service and inter-arrival time is not exponentially. The level of visitor arrivals was obtained for 13 people per 8 minutes. This means that the server is quite crowded by the customer and the service provided is also capable of serving pelanggan.Waktu customers waiting in the queue (Wq) is 0871 minutes and still be within the maximum limit of the customer is willing to wait (time aspiration) that is equal to 15 minutes.